Aciduric microbial taxa including Scardovia wiggsiae and Bifidobacterium spp. in caries and caries free subjects - Henne, Karsten; Rheinberg, Anke; Melzer-Krick, Beate; Conrads, Georg (Anaerobe, 2015)
Actinobacteria came into focus of being potential caries-associated pathogens and could, together with the established Streptococcus mutans and lactobacilli thus function as caries indicator species. Here we analyzed the role and diagnostic predictive value of the acidogenic–aciduric species Scardovia wiggsiae and Bifidobacterium dentium together with S. mutans, lactobacilli and bifidobacteria in biofilm of non-cavitated (n = 20) and cavitated (n = 6) caries lesions versus controls (n = 30). For the genus Bifidobacterium and for B. dentium new sets of primers were designed. Based on real-time quantitative PCR and confirmed by DNA sequencing we found a higher prevalence (61.5%) of S. wiggsiae in caries lesions than in controls (40%). However, among the controls we found three individuals with both the highest absolute and relative S. wiggsiae numbers. Testing for S. mutans revealed the same prevalence as S. wiggsiae in caries lesions (61.5%) but in controls its prevalence was only 10%. B. dentium was never found in healthy plaque but in 30.8% of clinical cases, with the highest numbers in cavitated lesions. The Bifidobacterium-genus specific PCR had less discriminative power as more control samples were positive. We calculated the relative abundances and applied receiver operating characteristic analyses. The top results of specificity (93% and 87%) and sensitivity (100% and 88%) were found when the constraint set was “Lactobacillus relative abundance ≥0.02%” and “two aciduric species with a relative abundance of each ≥0.007%”. Combinatory measurement of several aciduric taxa may be useful to reveal caries activity or even to predict caries progression. •For the detection of Bifidobacteria a new PCR protocol was developed.•Bifidobacterium dentium was never found in health but in 30.8% of caries cases.•Scardovia wiggsiae was found in health but its prevalence was elevated in caries.•Lactobacilli reached 100% sensitivity and 76.7% or higher specificity for caries.•Combinatory measurement of divers aciduric taxa is useful to reveal caries activity.